Adaptive Balancing Control of Cell Voltage in the Charging/Discharging Mode for Battery Energy Storage Systems - Wang, Yanfeng; Liu, Di; Shen, Yongpeng; Tang, Yaohua; Chen, Yanhui; Zhang, Junmin (Frontiers in Energy Research, 2022)
To improve the balancing time of battery energy storage systems with `cells decoupled and converters serial connected', a new cell voltage adaptive balancing control method in both charging and discharging modes is proposed in this paper. The overall system architecture and basic operating principle of the active balancing system with`cells decoupled and converters serial connected' are presented first. Then, by dynamically regulating the balancing acceleration coefficient of each cell according to the cell voltage deviation, the adaptive balancing control of cell voltage in charging and discharging modes is analyzed. An experimental prototype consisting of 6 smart cells is developed and experiments in charging and discharging modes were carried out. The experimental results demonstrate that compared with the balancing process with a static acceleration coefficient, the proposed adaptive balancing control of cell voltage shows significant improvement in balancing speed and smaller cell voltage discrepancy.